PENGARUH MOTIVASI DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DIMODERASI KOMITMEN ORGANISASIONAL - -, Sunarto (Dinamika Pendidikan, 2016)
Studi ini bertujuan untuk mengetahui dan menganalisis pengaruh motivasi dan kompetensi profesional terhadap kinerja guru dimoderasi komitmen organisasional guru di UPT Dindikbud Wiradesa Kabupaten Pekalongan. Jenis penelitian ini menggunakan penelitian lapangan (field research) dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah guru-guru yang mengajar di UPT Dindikbud Wiradesa Kabupaten Pekalongan berjumlah 125 orang dengan mengambil semua populasi. Teknik analisis menggunakan pengujian model analisis linier berganda, Uji R2, Uji F, pengujian hipotesis menggunakan uji t dan uji modereting. Hasil penelitian menunjukkan bahwa; (1) motivasi tidak berpengaruh terhadap kinerja guru (2) kompetensi profesional berpengaruh positif terhadap kinerja guru; (3) komitmen organisasional berpengaruh positif terhadap kinerja guru; (4) komitmen organisasional tidak memoderasi motivasi terhadap kinerja guru; (5) komitmen organisasional tidak memoderasi kompetensi profesional terhadap kinerja guru.Abstract The purposes of this study are to know and analyzed the motivation and professional competence on teachers performance are moderated by organizational teacher commitment in UPT of Education and Culture Department in Wiradesa, District of Pekalongan. This research uses field research with quantitative approach. The population of this research is all of the teachers are teach in UPT of Education and Culture Department in Wiradesa, District of Pekalongan which amount to 125 people and take all of them. Analysis technique uses multiple linear analysis model, R2 test, F test, hypothesis testing using t test and moderation test. The result showed that, (1) Motivation has not effect to the teachers performance. (2) Professional competence has positive effect to the teacher performance. (3) Organizational commitment has positive effect to the teacher performance. (4) Organizational commitment of moderated motivation on the teachers performance. (5) Organizational commitment of moderated professional competence on the teachers performance.Abstract The purposes of this study are to know and analyzed the motivation and professional competence on teachers performance are moderated by organizational teacher commitment in UPT of Education and Culture Department in Wiradesa, District of Pekalongan. This research uses field research with quantitative approach. The population of this research is all of the teachers are teach in UPT of Education and Culture Department in Wiradesa, District of Pekalongan which amount to 125 people and take all of them. Analysis technique uses multiple linear analysis model, R2 test, F test, hypothesis testing using t test and moderation test. The result showed that, (1) Motivation has not effect to the teachers performance. (2) Professional competence has positive effect to the teacher performance. (3) Organizational commitment has positive effect to the teacher performance. (4) Organizational commitment of moderated motivation on the teachers performance. (5) Organizational commitment of moderated professional competence on the teachers performance.